Developing Teaching Material in Natural Science Subject Using Inductive Thinking Models to Improve Critical Thinking of 4th Grade Students - Kosmita, Sri; Sukarno, Sukarno; Salamah, Salamah (IJIS Edu : Indonesian Journal of Integrated Science Education, 2020)
There are lack of science student worksheet based on inductive thinking in the education system are. So the purpose of this study is to create appropriate and good student worksheet teaching material using inductive thinking model in science learning, and to test whether there are differences in students' critical thinking by using science teaching materials based on inductive thinking model compared to conventional teaching materials in SDN 66 Kota Bengkulu. This type of research is R&D (Research and Developmet), which was developed using the Borg and Gall model proposed by Sugiyono. The instruments in this study werequestionnaire and essay test. The data analysis technique used is the "t" test. The results of the study that teaching materials are appropriate according to the material experts , teachers and the product is also good according to students. Teaching material about force in science using LKS based on inductive thinkingmodel can improve the critical thinking of SDN 66 students in Bengkulu City. This is also evidenced by the results of the "t" test obtained at sig 0.00 <0.05. Thus Ha is accepted and H0 is rejected, which means that there is a significant difference between students who use science teaching materials based on inductivethinking models with conventional teaching materials at SDN 66 Bengkulu City.